1993
DOI: 10.1103/physrevlett.71.2220
|View full text |Cite
|
Sign up to set email alerts
|

Transition of the radial electric field by electron cyclotron heating in the CHS heliotron/torsatron

Abstract: The transition of a radial electric field from a negative to a positive value is observed in the compact helical system when the electron loss is sufficiently enhanced by the superposition of the off-axis second harmonic electron cyclotron heating on the neutral beam heated plasmas. Existence of the threshold for the enhanced particle flux required to cause the transition is experimentally certified. The observed threshold is compared with a theoretical prediction. PACS numbers: 52.55.Hc, 52.50.Gj A radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…In stellarators with 3-dimensional flux surface geometry, collisional transport depends explicitly on the radial electric field which acts as drive for the radial fluxes and determines the transport coefficients. Therefore, the role of the electric field has always been of interest in stellarator research and stellarator theory has demonstrated the existence of branches with different ambipolarity conditions -the electron and the ion root [50] before CHS [51] and W7-AS [52] could verify this in the experiment.…”
Section: Understanding Of the H-mode [24 42 43]mentioning
confidence: 85%
“…In stellarators with 3-dimensional flux surface geometry, collisional transport depends explicitly on the radial electric field which acts as drive for the radial fluxes and determines the transport coefficients. Therefore, the role of the electric field has always been of interest in stellarator research and stellarator theory has demonstrated the existence of branches with different ambipolarity conditions -the electron and the ion root [50] before CHS [51] and W7-AS [52] could verify this in the experiment.…”
Section: Understanding Of the H-mode [24 42 43]mentioning
confidence: 85%
“…40 On the other hand, it was experimentally observed that a transition was forced to occur when ECR-heating of 140 kW was applied at the plasma periphery. 24 The result was explained by electron loss cone current enhanced by the ECR-heating.…”
Section: A Effect Of High Energy Particles On Pattern Formation In Pmentioning
confidence: 99%
“…23 After the charge exchange recombination spectroscopy ͑CXRS͒ was used to measure the internal radial electric field, 24 advanced measurements were performed using a heavy ion beam probe ͑HIBP͒. 25,26 The high spatio-temporal resolution of the HIBP was sufficient to reveal the bifurcation nature of the radial electric field.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been no experimental study to test these issues on the neoclassical ion transport in stellarator plasmas. This is because the transition of the radial electric field from small negative (ion root) to large positive (electron root) was observed only in plasmas with the assistance of electron cyclotron heating (ECH), where electron heating is dominant [7][8][9][10][11]. The ion temperature is much lower than the electron temperature because ions are heated only by the energy exchange between ions and electrons.…”
mentioning
confidence: 99%
“…In previous experiments [7][8][9][10][11], the transition from ion root to electron root was observed only in plasmas with ECH, therefore it has been also open to question as to whether the nonthermal electrons driven by ECH are required to achieve the transition. The transition of radial electric field from ion root to electron root clearly demonstrates that nonthermal electrons are not necessary for the transition, because there are no nonthermal electrons in NBI heated plasma.…”
mentioning
confidence: 99%